The Role of 9P Marketing Mix in Building Brand Equity of Murabahah Financing Products: An Islamic Value Perspective - Billah, Zahida I'tisoma; Fauziah, Olivia Hilmi (Journal of Economics and Social Sciences (JESS), 2025)
This study examines the implementation of the Islamic Marketing Mix 9P strategy in enhancing membership of murabaha financing products at BMT Maslahah Gending Branch, Probolinggo. Employing a qualitative case study approach through in-depth interviews, direct observation, and documentation, the research demonstrates that the applied marketing strategies align with Sharia principles and contribute significantly to the growth of membership. The effectiveness of the strategy is determined by service quality, transparency in profit margins, community-based educational initiatives, the institution’s trustworthy image, and internal staff synergy. Nevertheless, several challenges persist, including limited public literacy regarding Islamic finance, suboptimal utilization of social media platforms, and competition from conventional financial institutions. The findings suggest that sustained innovation in marketing approaches and intensified community education are essential for strengthening the competitiveness and sustainability of Islamic financial institutions.